STRATEGI PEMERINTAH DESA DALAM MENGEMBANGKAN POTENSI PERTANIAN DI DESA CIGANJENG KECAMATAN PADAHERANG KABUPATEN PANGANDARAN - Reihan Alif Setiawan; Irfan Nursetiawan; Dini Yuliani (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research is motivated by the village government's strategy in developing agricultural potential in Ciganjeng Village, Padaherang District, Pangandaran Regency which is not optimal. The purpose of this study is to determine the Village Government's Strategy in Developing Agricultural Potential in Ciganjeng Village, Padaherang District, Pangandaran Regency. The method used in this study is descriptive analysis. Informants are 7 people. Data collection techniques are literature study, field study (observation and interviews) and documentation. The author uses qualitative data analysis techniques through processing data from interviews and observations to draw conclusions so that they can answer the problems in the study. Based on the results of the study, it is known that the village government's strategy in developing agricultural potential in Ciganjeng Village, Padaherang District, Pangandaran Regency through five strategies with eight indicators studied is quite good but not optimal due to obstacles such as limited village budgets for the agricultural sector, low levels of education and skills of some farmers, and minimal access to modern agricultural technology and limited number and intensity of agricultural extension workers, limited farmer access to potential business actors to be invited to partner with and lack of farmer understanding of the importance of farmer institutions. Efforts include establishing partnerships with external parties, such as the Department of Agriculture and universities, to obtain technical assistance and assistance for agricultural programs. Increasing community participation by actively involving farmer groups in development planning meetings is also being undertaken. The village government is also striving to strengthen coordination with relevant agencies to ensure the sustainability of technical assistance and conducting intensive outreach and coaching to the community regarding the benefits of farmer groups and the importance of collaboration with business actors.